DEVELOPING CURRICULUM OF BACHELOR IN ELT PROGRAM BASED ON THE INDONESIAN NATIONAL QUALIFICATION FRAMEWORK (KKNI) - Latif, Amirudin (Universitas Muhammadiyah Metro, 2017)
The study is intended to develop curriculum of bachelor in ELT Program based on the Indonesian National Qualification Framework (KKNI). The procedure of the curriculum development is adapted from a guidance book of the curriculum development for higher education published by RISTEKDIKTI. The subjects of the study are the lecturers and students of English Department Muhammadiyah University of Metro, English teachers, headmaster, English course owners, heads of private and state institution, and heads of regency and city education office. The result of the study is the curriculum documents such as graduate profiles, learning outcomes, study materials, the structure of curriculum, the semesterly course distribution, course description, syllabus, and lesson plan. The curriculum has been implemented for two semesters. The students give positive responses on the implementation of the curriculum.